Speech Genre “Interpretation on Gospel”: Ideological Content and Linguo-Stylistic Features (Work of B. I. Gladkov) - A. N. Smolina; E. S. Smirnov (Научный диалог, 2023)
On the material of the texts of the spiritual writer B. I. Gladkov, the features of the implementation of the speech genre “interpretation of the Gospel” are considered. The specificity of the embodiment of the ideas of Orthodoxy is indicated. Significant features of the functioning of religions and tropes in the presented speech genre are revealed. Conclusions are drawn about its distinctive features. Particular attention is paid to the typology and functioning of Christian religions, the use of which is considered as one of the features of the church-religious functional style. The novelty of the study lies in the fact that for the first time it examines in detail the types of religions that exist in the genre of “interpretation of the Gospel”, provides illustrations of their use, indicates the functions they perform (characterological, emotive, evaluative, prescriptive, etc.). It has been established that in the analyzed texts the most common types of religion names are theonyms; biblonyms; hagioanthroponyms; names of biblical events; names of gospel heroes, etc. It is shown that the author’s use of a combination of such intra-genres as “opinion”, “comment-explanation”, “advice” belongs to the main features of the “interpretation of the Gospel” genre. The results of the study are of interest for theolinguistics, stylistics, and rhetoric.